Optimization of transport properties of poly (acrylamide-co-acrylic acid) based polymer electrolytes / Saminatha Kumaran Veloo - Saminatha Kumaran , Veloo (2022)
Over the last few decades, transport properties of solid polymer electrolytes play vital role in variety of electrochemical devices such as high energy density batteries, super capacitors, fuel cells, sensors, and dye-sensitized solar cells. Generally, solid polymer electrolytes have several advantages such as leakage-proof, lightweight, improved safety, inexpensive, good thermal stability, high flexibility, and ease of fabrication. In this research work, polymer electrolyte thin films based on Poly (acrylamide-co-acrylic acid) (PAAC) doped with Sodium Iodide (NaI) (System A) and system B was prepared by adding ionic liquid of 1-Butyl-3-Methylimidazolium Iodide (BMI) with optimized PAAC-NaI system in different ratios of polymer, salt, and ionic liquid by using solution casting method. In both Systems A and B, a fixed amount of additive of Propylene Carbonate (PC) was added to polymer electrolyte systems. The Propylene Carbonate (PC) was added to the mixture of the solution to provide more flexibility to the polymer film by increasing the plasticity of the thin film membrane. The conductivity and dielectric studies were carried out on these thin films over the wide range of frequencies from 50 Hz to 5 MHz to understand the ionic transport properties of the polymer electrolytes. The highest ionic conductivity has been found to be 1.88 × 10−5 Scm−1 for the system A optimized with 30 wt.% of NaI salt-doped polymer electrolyte system at room temperature and maximum ionic conductivity of 4.73 × 10−4 S cm−1 achieved for system B containing the optimized 30 wt. % NaI salt-doped polymer electrolyte and 15 wt.% BMI ionic liquid at room temperature. For both systems, the temperature dependent ionic conductivity agreed with Arrhenius relationship which shows the ion hopping mechanism of ions in the polymer matrix. The dielectric properties especially the loss tangent was analyzed to observe the segmental relaxation of the polymer chain upon incorporation of salt and ionic liquid. Further investigations were made to analyze the behaviour of thermally activated ionic diffusion and its overall effect on segmental dynamics of solid polymer electrolyte systems.